ANALISIS PENGARUH PERSEPSI KUALITAS LAYANAN DAN KEPUASAN MAHASISWA TERHADAP MINAT MEREFERENSIKAN KAMPUSNYA - Kurniawati, Dyah (Widya Warta, 2010)
Principally, the purpose of a business is to create customer’s satisfaction. The creation of customer’s satisfaction can provide several benefits, such as to preserve harmonious relationship between the company and the customer, to provide a good basis for the re-purchase and the creation of customer’s loyalty, and to establish beneficial recommendations from mouth to mouth. As a professional business unit, a university should implement marketing concepts, essentially giving satisfaction to its students. If it becomes a reality, the students will provide recommendations to their friends at senior high school to join the university. The result of the path analysis showed that the perception of service quality affected the students’ satisfaction, which, in turn, promoted the university. It can be stated that when students get a high quality service, they will feel satisfied and then recommend positive reference to others.